2022
DOI: 10.3389/fendo.2022.926769
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes of A549 Cells Induced Migration, Invasion, and EMT of BEAS-2B Cells Related to let-7c-5p and miR-181b-5p

Abstract: As carriers containing abundant biological information, exosomes could deliver the property of donor cells to recipient cells. Emerging studies have shown that tumor cells could secrete a mass of exosomes into the microenvironment to regulate bystander cells. However, the underlying mechanisms of such a phenomenon remain largely unexplored. In this research, we purified and identified the exosomes of A549 cells and found that A549-cell-derived exosomes promoted BEAS-2B cells migration, invasion, and epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 69 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…It is now generally accepted that cancer cell-derived EVs have the ability to promote cancer metastasis. Therefore, we evaluated the effect of EVs at 30 μg/mL on cancer cell migration and invasion and found no significant differences between AAW-promoted cancer cell-derived EVs and static cancer cell-derived EVs (Figure B,D,F,H,J). This result is consistent with previous studies in which EVs promote cancer cell migration and invasion . As a result, our findings indicate that the promotive function of EVs induced by the AAW method in facilitating cancer cell migration and invasion is maintained, which may help decipher the mechanism of EV-mediated cancer metastasis.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is now generally accepted that cancer cell-derived EVs have the ability to promote cancer metastasis. Therefore, we evaluated the effect of EVs at 30 μg/mL on cancer cell migration and invasion and found no significant differences between AAW-promoted cancer cell-derived EVs and static cancer cell-derived EVs (Figure B,D,F,H,J). This result is consistent with previous studies in which EVs promote cancer cell migration and invasion . As a result, our findings indicate that the promotive function of EVs induced by the AAW method in facilitating cancer cell migration and invasion is maintained, which may help decipher the mechanism of EV-mediated cancer metastasis.…”
Section: Resultssupporting
confidence: 93%
“…This result is consistent with previous studies in which EVs promote cancer cell migration and invasion. 51 As a result, our findings indicate that the promotive function of EVs induced by the AAW method in facilitating cancer cell migration and invasion is maintained, which may help decipher the mechanism of EV-mediated cancer metastasis. Thus, these results lay the foundation of enhancing EV production via AAW stimulation to boost cancer-EV-related basic research and translational investigation.…”
Section: Role Of Aaw-induced Evs On In Vitro Cancer Cell Migration An...mentioning
confidence: 67%
“…In this study, reduced E-cadherin and increased N Cadherin and Vimentin levels were observed in cells overexpressing STK36, which suggested an interaction between STK36 and EMT. EMT can accelerate the motility and migration of cancer cells besides their morphological alteration 37 , 38 . The CCK8 and cell wound scratch assay confirmed the claim.…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH served as endogenous reference of lncRNA and mRNA. ΔCt = Ct (target gene) ‒ Ct (GAPDH), ΔΔCt = ΔCt (treatment group) ‒ ΔCt (control group), and the relative expression of genes was calculated by formula 2 −ΔΔCt 44 . Table S1 displays the primers used in the study.…”
Section: Methodsmentioning
confidence: 99%